A Fast and Simple Method for the Analysis of Polymer Stabilizers Migrating from Polyolefin Foils Using Large-Volume-Injection HPLC with UV and Mass-spectrometric Detection - Emhofer, Lisa; W. Klampfl, Christian; Buchberger, Wolfgang (Current Analytical Chemistry, 2016)
A method for investigating migration of some of the most widely used polyolefin stabilizers into aqueous and ethanolic simulants is presented. Main advantage of the proposed approach is that concentrations down to 0.05 μg L-1 (Irganox 1010 and Irganox 1076) – 0.1 μg L-1 (Irgafos 168 and Irgafos 168ox) can be determined without any additional pre-concentration step. This is achieved via direct injection of 1000 μl of simulant onto the HPLC column. Due to the reduced number of working steps of the proposed protocol, this approach also helps to minimize the risk of contamination via contact with plastic material employed during analysis such as pipette tips or plastic SPE-cartridges. Large volume injection with either UV or MS2 detection allowed the sensitive determination of the selected stabilizers in food contact materials, whereby MS2 (employing electrospray ionization in the positive ion mode, nitrogen as collision gas and collision energies between 22 and 80V) provided slightly better LOD values. Migration of the selected stabilizers from polyolefin-based foils used for food storage and food processing into simulants could be verified down to levels of less than 10 ng per cm2 of foil.
Keywords: large volume injection